PENGARUH GLOBALISASI KEPADATAN PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP DEGRADASI LINGKUNGAN DI INDONESIA - Safriwan, Safriwan; Idris, Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract : The study describes the effects on globalization population density andeconomic growth on environmental degradation in Indonesia. This research uses a timeseries data from year 1971 - 2017, with method Error Correction Model (ECM). Datasources from Global Carbon Project, KOF Swiss Economic Institute, and WorldBank. Research result explain that (1) Globalization in long term has a insignificantpositive effect on environmental degradation in Indonesia, but short term globalizationhas a insignificant negative effect on environmental degradation in Indonesia (2)Population density in long term has a significant positive , and short term has ainsignificant positive effect on environmental degradation in Indonesia (3) Economicgrowth in long and short term has a significant positive effect on environmentaldegradation in Indonesia.Keywords : Environmental Degradation, Globalization Population Density AndEconomic Growth.